Rice Response to Potassium Fertilization in the Uruguayan Flooded Management System - Ferrando, Marcelo; Fernández, Mariano; Barbazán, Mónica M. (Agrociencia Uruguay, 2017)
Recent nutritional surveys and studies of response to the addition of potassium (K) in various non-irrigated crops have shown that this nutrient is one of the limitings of the crop production in Uruguay. In rice, although there is national information of studies of K fertilization, it is only for some varieties, with management practices different from the current ones, with non-consistent results. The aim of this study was to explore the response to K in commercial rice crops on sites located in the main area of rice production of Uruguay, the Laguna Merín Basin. During the crop season of 2011-12 and 2012-13, K-response trials were installed in three commercial rice crops in soils with 0.14, 0.19, and 0.25 cmol kg-1 exchangeable K, measured with acetate ammonium 1 M to pH 7. The treatments were four rates of K (30, 60, 120, and 240 kg ha-1 of K2O) applied as K chloride (KCl) plus a control, without K application. The total K concentration in leaves early in the season did not change significantly with K application, but the grain yield was increased (P < 0.02) in the three sites. The response was at the lowest doses applied, and the increases in grain yield ranged from 999 to 1375 kg ha-1. These results indicate the need to continue the studies on this nutrient in different rice production systems and associated soils.